The clutch athlete, choking and personality. Issue 1 (2nd January 2017) - Owens, Lynn; Stewart, Craig; Huebner, Eric
Abstract: The purpose of this work was to investigate personality as a component of "clutch" and "choking" performances of university athletes. The American Psychological Society defined personality as individual differences in … patterns of thinking, feeling and behaving. In studying personality, two broad areas arise; (1) the understanding of individual differences in particular personality characteristics and (2) understanding how the various parts of a person come together as a whole. In this study, a measurement of personality used more in the private business sector and a college head coach's identification of "clutch" players and those who have a tendency to "choke" were used in a qualitative comparison. The goal was to expand the practical application of personality theory to coaches in hopes of improving both coaches' understanding and players' performances.